2020
DOI: 10.3390/app10041234
|View full text |Cite
|
Sign up to set email alerts
|

Wavelia Breast Imaging: The Optical Breast Contour Detection Subsystem

Abstract: Wavelia is a low-power electromagnetic wave breast imaging device for breast cancer diagnosis, which consists of two subsystems, both performing non-invasive examinations: the Microwave Breast Imaging (MBI) subsystem and the Optical Breast Contour Detection (OBCD) subsystem. The Wavelia OBCD subsystem is a 3D scanning device using an infrared 3D stereoscopic camera, which performs an azimuthal scan to acquire 3D point clouds of the external surface of the breast. The OBCD subsystem aims at reconstructing fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The reflected, transmitted, and scattered signals are collected by the UWB antennas, digitized, and used in different imaging algorithms to recreate and reconstruct the target image. The scatterers (voids) and the surrounding areas cause scattering and show extra energy levels accordingly. …”
Section: Imaging Methodsmentioning
confidence: 99%
“…The reflected, transmitted, and scattered signals are collected by the UWB antennas, digitized, and used in different imaging algorithms to recreate and reconstruct the target image. The scatterers (voids) and the surrounding areas cause scattering and show extra energy levels accordingly. …”
Section: Imaging Methodsmentioning
confidence: 99%
“…Lower resolution in comparison with other modalities, as well as the many reconstruction artifacts that are related to the nonlinearity and ill-posedness of the associated inverse problem, are the main reasons that MWI is not clinically accepted yet. Although it has been shown that using accurate prior information will reduce the Root-Mean-Squared (RMS) reconstruction error over the whole image [ 9 , 10 , 30 , 31 , 32 ], artifacts and reconstruction errors near the tumor can translate to poor tumor detection results [ 33 ].…”
Section: 3d Csi-deep-learning Methodologymentioning
confidence: 99%
“…Alió, published in March 2020, described a graphical user interface helping specialists to detect RETCS disease, assisted by artificial intelligence. • "Wavelia Breast Imaging: The Optical Breast Contour Detection Subsystem" [7] by Julio Daniel Gil Cano, Angie Fasoula, Luc Duchesne, and Jean-Gael Bernard was published in February 2020 and described a tool to help specialists in analyzing breast images to detect anomalies and better establish a relationship between disease and deformities.…”
Section: Decision Support Tools In Biomedical Applicationsmentioning
confidence: 99%